482 Is Subspecialisation Important for Emergency Laparotomy Outcomes?. (12th October 2021) - Chowdhury, S; Musbahi, A; Agarwal, A
Abstract: Introduction: High mortality and morbidity is associated with Emergency Laparotomy. This study looks at outcomes of different subspecialties of surgeons performing Emergency Laparotomies identified from National Emergency Laparotomy Audit (NELA). Method: All NELA entries in North Tees Hospital from Jan 2014 to Jan 2019 extracted and reviewed, supplemented with local medical records. Data divided into specialist areas of breast, colorectal and UGI specialist groups with 784 laparotomies in total, 384 M (49%), 400 F (51%). Range of categorical variables pre, peri and post operatively looked at to determine operative management. Results: Colorectal surgeons more likely to complete procedure laparoscopic/laparoscopic assisted. No statistical difference in conversion of Laparaoscopy, A significant difference in mean length of stay days for patients treated by a breast and UGI specialist (Mean Difference = -0.23, p = .005). Patients treated by UGI specialist had a longer length of stay. Significant difference in number of days critical care admission for breast specialists and colorectal (Mean Difference = -0.20, p = .025) and UGI (Mean Difference = 0.22, p = .013). Significant difference in mean time to theatre (hours) for patients treated by a UGI and colorectal specialist (Mean Difference = -0.36, p = .002). Specifically, patients treated by a colorectal specialist had longer time to theatre than patients treated by a UGI specialist. Conclusions: Surgical outcomes are seen to be better with UGI and colorectal emergency laparotomies, with significant difference in post-operative management of patients. Current evidence suggests, a need for emergency surgery as a subspecialty.